2021
DOI: 10.1103/physrevb.103.115127
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of electronic structure and surface reconstruction in the superionic Cu2xTe

Abstract: Recently, layered copper chalcogenides Cu2X family (X=S, Se, Te) has attracted tremendous research interests due to their high thermoelectric (TE) performance, which is partly due to the superionic behavior of mobile Cu ions, making these compounds "phonon liquids". Here, we systematically investigate the electronic structure and its temperature evolution of the less studied single crystal Cu2-xTe by the combination of angle resolved photoemission spectroscopy (ARPES) and scanning tunneling microscope/spectros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…structure with respect to different substrates, [17][18][19] but two lattice-matched distinct phases were also reported in Cu2Te monolayer growth via the vapor-liquid-solid (VLS) method. [20] Chen et al observed a 2×2 surface reconstruction on Cu2−𝑥Te single crystal through spectroscopy measurements, but multiple other types of reconstruction patterns were detected meanwhile.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…structure with respect to different substrates, [17][18][19] but two lattice-matched distinct phases were also reported in Cu2Te monolayer growth via the vapor-liquid-solid (VLS) method. [20] Chen et al observed a 2×2 surface reconstruction on Cu2−𝑥Te single crystal through spectroscopy measurements, but multiple other types of reconstruction patterns were detected meanwhile.…”
mentioning
confidence: 77%
“…1(b), the lattice parameters are identified with 𝑎0 = 𝑏0 = 4.186 Å, 𝑐0 = 7.232 Å and 𝛼 = 𝛽 = 90 ∘ , 𝛾 = 120 ∘ , which are consistent with the previous reports. [15,[18][19][20]22] The estimated layer spacing revealed by atomic force microscopy (AFM) is about 7 ± 0.5 Å as shown in Figs. S1(b) and S1(c) in the Supplementary Materials (SM).…”
mentioning
confidence: 98%
See 3 more Smart Citations